Strategic Cyber Public Relations: A Case Study of PT PLN Nusantara Power’s Engagement on Instagram - Teguh, Monika; Dafa, Muhammad; Aji, Imanuel Deny Krisna; Sistiawan, Ivana Clairine (Universitas Ahmad Dahlan, 2023)
In the wake of the COVID-19 pandemic, digital communication channels, particularly social media platforms, have become pivotal for organizations worldwide. This study presents a detailed analysis of PT PLN Nusantara Power’s (PT PLN NP) strategic Cyber Public Relations (PR) activities on Instagram. PT PLN NP, a leading energy company in Indonesia, adeptly navigated the digital landscape, earning recognition as the